African appropriations : cultural difference, mimesis, and media - Krings, Matthias, 1967 September 26- (African expressive cultures., 2015)
Why would a Hollywood film become a Nigerian video remake, a Tanzanian comic book, or a Congolese music video? Matthias Krings explores the myriad ways Africans respond to the relentless onslaught of global culture. He seeks out places where they have adapted pervasive cultural forms to their own purposes as photo novels, comic books, songs, posters, and even scam letters. These African appropriations reveal the broad scope of cultural mediation that is characteristic of our hyperlinked age. Krings argues that there is no longer an "original" or "faithful copy," but only endless transformations that thrive in the fertile ground of African popular culture.